2008
DOI: 10.1021/jo702633g
|View full text |Cite
|
Sign up to set email alerts
|

The Newman−Kwart Rearrangement:  A Microwave Kinetic Study

Abstract: The kinetic profile of the Newman-Kwart rearrangement has been evaluated using microwave heating. After first demonstrating equivalence between conventional convective heating and microwave heating, data was gathered and analyzed to determine the effects of substituent, solvent, and concentration on the reaction order. Reaction rate constants, Arrhenius constants, and activation energies have been determined. The reaction rate shows strong sensitivity to the substituent and modest sensitivity to the solvent. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 18 publications
6
46
0
Order By: Relevance
“…To gain insight to the course of the reaction the kinetics for the rearrangement of 4-nitro-O-aryl selenocarbamate (2 c) was studied and compared with previously reported results obtained with 4-nitro-O-arylthiocarbamate. [18] It was found that both the O Ar !S Ar and the experimental O Ar !Se Ar rearrangement proceeds with first-order kinetics and a comparison of the kinetic parameters are presented in Figure 2. Here it is shown how the O Ar !Se Ar proceeds significantly faster than the O Ar !S Ar rearrangement.…”
mentioning
confidence: 99%
“…To gain insight to the course of the reaction the kinetics for the rearrangement of 4-nitro-O-aryl selenocarbamate (2 c) was studied and compared with previously reported results obtained with 4-nitro-O-arylthiocarbamate. [18] It was found that both the O Ar !S Ar and the experimental O Ar !Se Ar rearrangement proceeds with first-order kinetics and a comparison of the kinetic parameters are presented in Figure 2. Here it is shown how the O Ar !Se Ar proceeds significantly faster than the O Ar !S Ar rearrangement.…”
mentioning
confidence: 99%
“…the non-existence of non-thermal microwave effects. [35][36][37][38][39][40] In addition, comparable polydispersity indices were obtained for the thermal and microwave polymerizations, indicating a similar control over the polymerizations.…”
Section: Comparison Of Microwave and Thermal Heatingmentioning
confidence: 58%
“…Furthermore, the O Ar →Se Ar rearrangement reaction also proceeds at significantly lower temperatures than does the O Ar →S Ar rearrangement when the same phenols are used. To gain insight to the course of the reaction the kinetics for the rearrangement of 4‐nitro– O ‐aryl selenocarbamate ( 2 c ) was studied and compared with previously reported results obtained with 4‐nitro‐ O‐ arylthiocarbamate 18. It was found that both the O Ar →S Ar and the experimental O Ar →Se Ar rearrangement proceeds with first‐order kinetics and a comparison of the kinetic parameters are presented in Figure 2.…”
Section: Methodsmentioning
confidence: 95%